2011
DOI: 10.1083/jcb.201103118
|View full text |Cite
|
Sign up to set email alerts
|

Polytopic membrane protein folding at L17 in the ribosome tunnel initiates cyclical changes at the translocon

Abstract: Interaction between L17 in the ribosome tunnel and folded nascent chain transmembrane segments during multi-spanning membrane protein synthesis triggers structural rearrangements in the ribosome that cause switching between cytosolic and ER lumenal targeting of the growing polypeptide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 79 publications
(172 reference statements)
1
35
0
Order By: Relevance
“…The efficiency of transfer, E, depends on several variables, but most importantly on the distance between donor and acceptor. Most FRET experiments measure and/or monitor the separation between a single donor dye and a single acceptor dye at specific sites in the same molecule (e.g., Woolhead et al, 2004; Lin et al, 2011b) or molecular complex (e.g., Johnson et al, 1982). However, protein interactions and topography at the two-dimensional membrane surface are sometimes characterized using a variation of the FRET technique that introduces acceptor-labeled PL molecules into liposomes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The efficiency of transfer, E, depends on several variables, but most importantly on the distance between donor and acceptor. Most FRET experiments measure and/or monitor the separation between a single donor dye and a single acceptor dye at specific sites in the same molecule (e.g., Woolhead et al, 2004; Lin et al, 2011b) or molecular complex (e.g., Johnson et al, 1982). However, protein interactions and topography at the two-dimensional membrane surface are sometimes characterized using a variation of the FRET technique that introduces acceptor-labeled PL molecules into liposomes.…”
Section: Resultsmentioning
confidence: 99%
“…We have not attempted to estimate the BOP-PE σ in KRMs because the amount and disposition of surface area occupied by proteins is unknown, as is the extent and distribution of BOP-PE association with ER membrane proteins. But the R 0 for NBD-BOP FRET is 47 Å (Lin et al, 2011b) and the translocon diameter is ~100 Å in native ER membranes (Hanein et al, 1996), so E between an NBD and a BOP on opposite sides of a translocon is essentially 0.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the ribosome was implicated in influencing the translocon with respect to TM integration and pore sealing (e.g., refs. [16][17][18]. Molecular dynamics (MD) analysis suggested that modulation of the channel's gating kinetics is controlled by the TM's hydrophobicity (19)(20)(21).…”
mentioning
confidence: 99%
“…The endoplasmic reticulum and the bacterial transport systems address these problems by co-translational integration. This presumably avoids aggregations of the multiple hydrophobic segments in the aqueous compartment and also may choreograph stepwise insertion of TMDs [6365]. In E. coli the signal recognition particle (SRP), which consists of an SRP54 homologous protein and a 4.5 S RNA (Figure 4-B), binds the signal peptide or amino proximal TMD emerging from the ribosomal tunnel and escorts the nascent chain-ribosome complex to SecYEG, to YidC, or to a complex of both for co-translational integration [5,66].…”
Section: Membrane Protein Integrationmentioning
confidence: 99%